Listening to the Student Voice: Understanding the school-related factors that limit student success - Segedin, Lauren (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2012)
Literature on social inequalities in schooling reveals that the school curriculum, streaming, and teacher expectations are school-related factors that limit student success. This study asks: How do the school curriculum, streaming and teacher expectations limit students who have been designated “at risk” from finding success in school? Quantitative and qualitative data showed that the curriculum does not meet all students’ needs, streaming diminishes learning, and low teacher expectations limit student success. Student self-blame and meritocracy are other factors found to limit student success.